A Conversational Reflection on the Co-Creation of the Principal Preparation Answerability Rubric (PPAR) - Stewart, Nathaniel D.; Bigirindavyi, Malaika (Radical Teacher, 2025)
The purpose of this piece is to offer educational leadership program officers and educators a collective assessment tool that can be used to evaluate the extent to which licensure curriculum meets a critical diversity, equity, and inclusion (DEI) framework. Principal preparation programs are held accountable to state-level requirements formulated by the perspectives of previous school leaders and current state legislatures. State-level principal preparation and DEI accountability can still miss the dynamic lived experiences of racialized and marginalized students and teachers. This article aims to center the perspectives of Black, Brown, and Indigenous students and teachers by providing a tool that can be used in systematic evaluations of principal preparation programs. The Principal Preparation Answerability Rubric (PPAR) was co-created by Joy, guided by Dr. Chadwick, to assess principal preparation syllabi and other pedagogical materials. We co-created the PPAR from a literature review uplifting the needs, recommendations, and critiques Black, Brown, and Indigenous students and teachers have regarding principals in their roles as local-level leaders. It is from Black, Brown, and Indigenous knowledges that we interpreted the answerability rubric categories. We argue principal preparation can be answerable to those people who are neglected by US educational systems. We conclude in implicating how PPAR can contribute to reimagining principal preparation through critical DEI frameworks. This is a correction to the original article. For information about the changes made, please see the erratum linked as a supplemental file on the article’s landing page. The information will also be available at https://radicalteacher.library.pitt.edu/ojs/radicalteacher/article/view/1397 in issue 132.